Status Terkini Tutupan Terumbu Karang di Perairan Dangkal Pulau Bedil, Desa Labuan Bajo, Kabupaten Sumbawa, NTB - Mahardika Rizqi Himawan; Eni Hidayati; Nurliah Buhari; Sitti Hilyana; Maulita Syahdina (LPPM Universitas Mataram, 2021)
Bedil Island is included in the Keramat, Bedil, and Temudong Small Island Park (TPK), which was approved by the Regent of Sumbawa. Administratively, this island is included in the Labuan Bajo Village area, Sumbawa, NTB. There is the existence of coral reef ecosystems in these waters that form a reef flat and reef slope profile, that stretches to the southwest and northeast. By its designation as a small island park, the coral reefs in Bedil Island are used as an underwater tourism object. This study aims to determine the current condition of coral reef cover in the waters around Bedil Island, especially in the eastern and southern parts of the island. Coral reefs in the north and west area are limited and there is the existence of seagrass beds. The line intercept transect method is carried out by spreading the roll meter as far as 50 meters on the east and south sides of the island with a depth of 2-3 meters. The coral lifeform that is tangent with the roll meter is then recorded and then analyzed for the average percent cover, clustering status, and coral mortality index. Coral reefs in the eastern and southern parts of Bedil Island are classified as very good/excellent because they have a percent cover value above 75%. In addition, the coral mortality index value is also relatively small which indicates that the corals are living well. Clearwater conditions and locations far from human settlements are thought to be factors that support coral survival. However, the presence of dead coral algae and rubble still indicates a threat of damage even though the value is small. Algae life on the surface of dead coral also indicates that the coral has been dead for a long time.